Policies, legislation and organizations related to water in South Africa, with special reference to the Olifants River Basin - Thompson, H.; Stimie, C.M.; Richters, E.; Perret, S. (International Water Management Institute, 2001)
The study is reported in two Working Papers. Working Paper 17 reports the findings of the HIM exercise. This paper contains the policies, legislation and organizations relevant for understanding of the HIM for the Olifants river basin. It also includes the historical development of the institutional framework in the basin, as this history has left a profound imprint on the South African society at large and is still dictating, in many cases, the interactions between the different organizations. This background on previous and current institutions and policies at the different government levels is used to shed light on the current relationships between different organizations in the basin. Although focusing on the Olifants, the description provided is applicable to the rest of South Africa in broad terms.